Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Pasien Non Bpjs di Klinik Abadi Jaya Depok - B. Retno Pratiwi S; Vivi Ristanti (Peneliti.net, 2022)
This study aims to determine the effect of service quality and facilities on patient satisfaction in choosing a health clinic, at the Abadi Jaya Clinic, Depok. Respondents in this study were 100 non BPJS patients who seek treatment at the Abadi Jaya Clinic, Depok. Based on the data that has been collected and the tests carried out using the t-test analysis method, coefficient of determination, correlation, regression, it can be concluded as follows: 1) All instruments are service quality variables (X1), facilities (X2), and patient satisfaction ( Y) has a CITC value greater than 0.3. This shows that each statement on service quality, facilities, and patient satisfaction is reliable and worthy of use as research. 2) Based on the results of the analysis, the value of Cronbach's Alpha on the service quality variable (X1) is 0.780. Facility (X2) is 0.780. and patient satisfaction (Y) of 0.779. Thus it can be concluded that all variables in this study are reliable, because they have Cronbach's Alpha values above 0.6.3). Service quality has an influence on patient satisfaction in choosing Abadi Jaya Clinic by 0.857 or 85.7% and the remaining 14.3% is influenced by other factors. 4). Facilities have an influence on patient satisfaction in choosing Abadi Jaya Clinic by 0.880 or 88.0% and the remaining 12.0% is influenced by other factors. 5). The quality of service and facilities together has an influence on patient satisfaction in choosing the Abadi Jaya Clinic by 0.884 or 88.4% and the remaining 11.6 is influenced by other factors.